Analysis Of Reservation Resources To Increase Room Sales At Kayumanis Jimbaran Private Estate & Spa - Adipratama, I Wayan Resa; Sutarma, I Gusti Putu; Susyarini, Ni Putu Wiwiek Ary (Jurnal Sains Terapan Pariwisata, 2022)
Purpose: This research aims to determine the contribution of reservations through reservation sources to increase room sales at Kayumanis Jimbaran Private Estate & Spa. To find out the gift of each reservation most dominant on the room sales rate.Methods: Data sources are reservation data from online travel agents, offline travel agents, and direct booking, as well as data related to room sales rates from January 2019 to December 2020. Methods of data collection are done through interviews and documentation. Data analysis uses simple descriptive statistical analysis techniques.Implication: The strategy that stimulates the success of several online and offline travel agents is through efforts to provide commission rewards and benefits such as FOC (Free of Charge) promo packages.